A rare Zinner syndrome combined with testicular cancer: a case report - Meng, Linghao; Shao, Yanxiang; Jia, Yige; Deng, Xiangfei; Tang, Yaxiong; Hu, Xu; Wu, Kan; Li, Xiang (Frontiers in Oncology, 2025)
BackgroundZinner syndrome is a rare congenital disorder of the urogenital system. In current reports, cases of Zinner syndrome complicated by malignant tumors are even rarer.Case descriptionWe reported a 26-year-old male with Zinner syndrome complicated by testicular embryonal carcinoma and retroperitoneal lymph node metastasis. He received orchiectomy, chemotherapy and a retroperitoneal lymph node dissection with favorable response.ConclusionsAs suggested by this rare case, Zinner syndrome may be bound up with genitourinary malignancy tumor. When diagnosing congenital disorders of the urinary system, it is essential for clinicians to take into consideration potential complications. More importantly, it is also paramount to account for the similarities and differences in diagnosis and treatment between comorbid and isolated conditions.